2020
DOI: 10.1108/ijchm-09-2019-0773
|View full text |Cite
|
Sign up to set email alerts
|

Testing moderating effects on the relationships among on-board cruise environment, satisfaction, perceived value and behavioral intentions

Abstract: Purpose This study aims to investigate both the relationships among the on-board environment, overall satisfaction, perceived value and behavioral intentions and the moderating effects of gender, employment status, group composition and the propensity to stay on board in the context of cruise experience. Design/methodology/approach Relationships among constructs were tested on the basis of 417 surveys collected and analyzed with the structural equation modeling approach of partial least squares path modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 62 publications
3
35
0
4
Order By: Relevance
“…The nature of mediation is identified to be a partial mediation, and study findings are in line with the results obtained from previous research work (Aljumah et al, 2020;Cronin et al, 2000;Slack and Singh, 2020) indicating that this study for medical care in Maldives shows a similar pattern to that of health care in the Malaysian medical tourism, healthcare in the USA, and Fiji supermarkets. This study confirms that service quality has both direct and indirect effects on behavioural intention in medical care among Maldivians pursuing medical care, indicating agreement with previous researches of Italian cruise ship passengers (Calza et al, 2020), that of the restaurant industry in Indonesia (Andriano et al, 2019), and the telecommunication industry in Jordan (Harazneh et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The nature of mediation is identified to be a partial mediation, and study findings are in line with the results obtained from previous research work (Aljumah et al, 2020;Cronin et al, 2000;Slack and Singh, 2020) indicating that this study for medical care in Maldives shows a similar pattern to that of health care in the Malaysian medical tourism, healthcare in the USA, and Fiji supermarkets. This study confirms that service quality has both direct and indirect effects on behavioural intention in medical care among Maldivians pursuing medical care, indicating agreement with previous researches of Italian cruise ship passengers (Calza et al, 2020), that of the restaurant industry in Indonesia (Andriano et al, 2019), and the telecommunication industry in Jordan (Harazneh et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Slack and Singh (2020) conducted a study of Fiji supermarkets and identifies that service quality significantly affects customer satisfaction, and service quality effects customer loyalty, and customer satisfaction partially mediates the relationship between service quality and customer loyalty. Calza et al, (2020) conducted a study in Italy on cruise ships' environment, and find out that all the interrelationships between customer satisfaction, perceived value, and behavioural intention are supported, indicating that the overall customer satisfaction influences behavioural intention significantly. Aljumah et al, (2020) found that satisfaction mediates the relationship between service quality and patient loyalty among foreign patients in Malaysian medical tourism.…”
Section: The Relationship Between Service Quality Customer Satisfaction and Behavioural Intentionmentioning
confidence: 99%
“…the "shipscape") and cruise services is limited (Han and Hyun, 2019). Given that cruise ships are bounded spaces in which consumers want to relax and be comfortable (Ahn and Back, 2019;Calza et al, 2020;Chen et al, 2016), these amplify crowding's negative effects, specifically those of large ships . Cruises could simultaneously be interpreted as a hedonic, experiential and symbolic service, whose functional goal is not very important (Han and Hyun, 2019), making perceived crowding's role less negative for various profiles.…”
Section: Crowdingmentioning
confidence: 99%
“…‫العميل‬ ‫رصا‬ Oliver, 1997, Das et al, 2019 ‫التيارة‬ ‫إعادة‬ ‫نوايا‬ Kim & Moon, 2009;Mannan et al, 2019 ‫نش‬ (Park et al, 2019;Torlak et al, 2019;Dwaikat et al, 2019;Calza et al, 2020 (Cambra-Fierro et al, 2017;Mishra, 2016;Chou & Chen, 2018;Huggins et al, 2020;Dekhili & Hallem, 2020;Assiouras et al, 2019;Grott et al, Mediating customer gratitude and satisfaction in the relationship between value co-creation and positive behavioral intentions of hotel's customers in Egypt: The moderating role of price fairness perception.…”
mentioning
confidence: 99%
“…( ‫علي‬ ‫ـتينامية‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫اس‬ ‫ـعار‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫س‬ ‫لدفع‬ ‫العمالر‬ ‫ـتعداد‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫اس‬ Homburg et al, 2005 ‫ويؤكد‬ .) (Konuk, 2019) ‫وجود‬ ‫علي‬ ‫املنطوقة‬ ‫الكلمة‬ ‫علي‬ ‫العميل‬ ‫ـا‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫لرص‬ ‫معنو‬ ‫تيثير‬ ‫التيارة.‬ ‫إعادة‬ ‫واحتمالية‬ ‫ـا‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫لرص‬ ‫إيجابي‬ ‫معنو‬ ‫تيثير‬ ‫يوجد‬ ‫كما‬ ‫عام‬ ‫ـكل‬ ‫بش‬ ‫الفنادق‬ ‫لعمالر‬ ‫ـلوكية‬ ‫الس‬ ‫النوايا‬ ‫على‬ ‫العمالر‬(Park et al, 2019;Torlak et al, 2019;Dwaikat et al, 2019;Calza et al, 2020) ‫وقد‬ . ‫اجعا‬ ‫ملر‬ ‫ـم‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫الحاس‬ ‫الدور‬ ‫على‬ ‫ـور‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫الض‬ ‫ـاطقة‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫الس‬ ‫ـيافة‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫الض‬ ‫طحاث‬ ‫ـلط‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫س‬ ‫ت‬ ‫ال‬ ‫ـاع‬ ‫ـ‬ ‫قط‬ ‫ـاق‬ ‫ـ‬ ‫ـي‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫س‬ ‫في‬ ‫العمالر‬ ‫ـة‬ ‫ـ‬ ‫ـاف‬ ‫ـ‬ ‫ـي‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ـ‬ ‫ض‬ (Wu et al, 2016; Sharifi, 2018; Lee & Kim, 2020) ‫ـة‬ ‫ـ‬ ‫نظري‬ ‫على‬ ً ‫ـار‬ ‫ـ‬ ‫وهن‬ .…”
unclassified